Transforming Science Education Globally Through Electronic Worksheets' Cognitive Impact: Mengubah Pendidikan Sains Secara Global Melalui Dampak Kognitif Lembar Kerja Elektronik - Aida, Wafid; Wulandari, Ria (Indonesian Journal of Education Methods Development, 2024)
This study investigates the impact of using electronic worksheets on students' cognitive learning outcomes in understanding the human digestive system. Conducted at SMPN 3 Porong with Grade VIII students, the research employed a quantitative approach with Quasi Experimental Design and Non-equivalent Control Group Design. The experimental class (VIII F) used electronic worksheets, while the control class (VIII G) did not. Pretests and posttests were administered, showing a significant improvement in cognitive learning outcomes in the experimental class compared to the control. These findings highlight the potential of electronic tools in enhancing student learning experiences in science education, particularly in complex subjects like biology. Highlight: Enhanced learning with electronic worksheets in science education. Quasi-experimental design compares electronic and traditional methods. Technology integration improves student engagement and cognitive outcomes. Keyword: Electronic Worksheets, Cognitive Learning Outcomes, Science Education, Quasi Experimental Design, Student Engagement